Relation among velocity of lightning travelling wave, lightning stroke current, and tower footing resistance to study back-flashover on the insulators in transmission tower - Pothisarn, C.; Thongsuk, S. (My University, 2013)
This paper studies the impact of back-flashover on the insulators with various velocities of lightning travelling wave, the lightning stroke current, and the tower footing resistance. The impedance of transmission tower section such as top tower, upper phase, middle phase, and lower phase that is calculated with lightning velocity dependent parameters is also considered. The velocity of lightning travelling wave at 300 m/μs and 200 m/μs is compared to consider back-flashover including maximum voltage at the cross arm and voltage across insulators. The results is shown that the velocity of lightning travelling wave plays an important role for the back-flashover voltage across insulator as well as the tower footing resistance and the lightning stroke current. © 2013 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Back-flashover; Lightning surge; Transmission tower; Travelling wave